The Firstborn is Dead: Infanticide in the Academy. Issue 5 (13th April 2017) - Stone, Duncan
Abstract: Why is sport history, despite the central position it plays in the examination of core issues such as gender, race, nationalism and other identities, still marginalized within the historical discipline? This brief reflection on the subject suggests – in broad terms – that this remains the case because many practitioners lack the ambition, or the imagination, to break free from well-worn areas of research and publication outlets. If sports historians consistently fail to recognize opportunities to examine new topics and publish in high-ranking non-sport journals, the historical 'mainstream' will continue to refer to 'classic', yet outdated, texts that ultimately demean both parties. As shown in the article, this blinkered approach is exacerbated by current trends in higher education funding and recruitment.